IMPLEMENTATION OF PROVISION OF LEGAL PROTECTION FOR BUYERS FOR WARRANTY OF GOODS IN THE COUNTRY OF INDONESIA - Syaparuddin (GoAcademica Research dan Publishing, 2022)
This research will be carried out to see how the implementation of consumer protection in obtaining goods guarantees in the eyes of business law and what the consequences are if the warranty received is not in line with Law No. 8 of 1999 concerning Consumer Protection. This research will use a normative juridical approach and secondary research data. The research data that has been collected will be processed and analyzed qualitatively. The results of this study found that many people experienced losses as a result of seller fraud against the guarantees given to consumers. This causes the need for the government to make various regulations to be able to provide guarantees of protection to the public who become consumers. The form of government regulation that has been successfully made is UUPK. Unfortunately, this regulation still has a lot of deviations and losses that the government feels, so the results are not optimal. Meanwhile, criminal sanctions will be given to business actors who violate the guarantee of their property if it does not follow the UUPK.